2012
DOI: 10.1088/1468-6996/13/5/054302
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic excitations in iron chalcogenide superconductors

Abstract: Nuclear magnetic resonance and neutron scattering experiments in iron chalcogenide superconductors are reviewed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 83 publications
(110 reference statements)
0
14
0
Order By: Relevance
“…This scenario matches with the experimental [46][47][48] and theoretical [49] findings that in FeTe the Fe moments align according to a magnetic wave vector (π ,0), in contrast with the AFM order along the nesting wave vector (π ,π ) of 1111 and 122 parent compounds. While the (π ,π ) spin fluctuations couple with carriers [50,51], (π ,0) spin fluctuations are not expected to, because they do not match any nesting wave vector [52,53]. This is observed in Fe 1+x Te 0.7 Se 0.3 superconducting samples where with increasing the interstitial iron concentration (x), (π ,π ) spin fluctuations disappear in favor of (π ,0) spin fluctuations and superconductivity disappears [54].We predict that, in principle, also FeTe devoided of interstitial iron should exhibit magnon drag Seebeck contribution.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…This scenario matches with the experimental [46][47][48] and theoretical [49] findings that in FeTe the Fe moments align according to a magnetic wave vector (π ,0), in contrast with the AFM order along the nesting wave vector (π ,π ) of 1111 and 122 parent compounds. While the (π ,π ) spin fluctuations couple with carriers [50,51], (π ,0) spin fluctuations are not expected to, because they do not match any nesting wave vector [52,53]. This is observed in Fe 1+x Te 0.7 Se 0.3 superconducting samples where with increasing the interstitial iron concentration (x), (π ,π ) spin fluctuations disappear in favor of (π ,0) spin fluctuations and superconductivity disappears [54].We predict that, in principle, also FeTe devoided of interstitial iron should exhibit magnon drag Seebeck contribution.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…In FeSe, the absence of long-range magnetic order despite the presence of nematic order [123] is striking and resulted in a large interest [58] in this purely nematic state and its interrelation with superconductivity. Given that strong magnetic fluctuations were observed at ambient pressure, [124][125][126][127][128][129] the "sought-for" magnetically ordered ground state was found to be stabilized in FeSe by the application of modest hydrostatic pressure, p ≳ 0.9 GPa, as first demonstrated by muon spin resonance ( SR) measurements under pressure. [62] This observation initiated ideas that the phase diagram of FeSe might depict features which are compatible with the universal phase diagram of iron-based superconductors [130,131] and therefore might still be consistent with a magnetically driven mechanism for nematicity and superconductivity.…”
Section: Phase Diagram Of Fese Under Hydrostatic Pressurementioning
confidence: 94%
“…Despite the absence of long-range magnetic order at ambient pressure, strong magnetic fluctuations of both stripe-type and Néel-type were detected. [124][125][126][127][128][129] Upon cooling through T s at ambient pressure, the spectral weight of the magnetic fluctuations is shifted toward lower energies and toward stripe type order. Since NMR measurements revealed that magnetic fluctuations become only strongly enhanced below T s , it was suggested that orbital order is the driver of nematicity at ambient pressure.…”
Section: Phase Diagram Of Fese Under Hydrostatic Pressurementioning
confidence: 99%
“…Hints to the microscopic origins of magnetic correlations in FeSe can be found in the complex temperature and momentum dependence of magnetic fluctuations, and its imprints on the nematic state and superconductivity; see Section 3.3.5 below. Experimentally, these correlations have been studied using NMR and inelastic neutron scattering experiments [144,[151][152][153][154][155][156], with the latter summarized in Figure 7. In the spin nematic scenario, these fluctuations are argued to drive the nematic order, eventually leading to a divergence of the nematic susceptibility.…”
Section: Spin Fluctuations In Normal Statementioning
confidence: 99%